P2-S2.04 Sex workers, mobility and migrant Latino men in the US South: findings from an exploratory rapid ethnographic assessment in North Carolina. (10th July 2011) - Kroeger, K; Sangaramoorthy, T; Vallila-Buchman, P; Robitz, R; Moore, P; Clymore, J
Abstract : Background: A growing number of studies indicate frequent use of female sex workers among migrant Latino men in the US South, yet little is known about the context in which sex workers and clients interact, or the women who provide these services. The Latino population in North Carolina has increased 400% since 1990; most of these are young, unaccompanied migrant men. HIV rates are four times higher for Latinos than for whites, yet very little is known about the risk factors that affect HIV/STD transmission within this population. To better understand the typology of sex work services available to Latino men in North Carolina, and the potential for HIV/STD transmission among sex workers and their clients, we conducted a rapid ethnographic assessment. Methods: We conducted 28 key informant interviews and field observations in four counties in May 2010. We asked key informants from state and local HIV/STD and rural/migrant health programs, community based organizations and law enforcement/legal aid agencies to describe the typology of sex work, mobility patterns of women involved in sex work, HIV/STD risk behaviours of sex workers and their Latino male clients, and the availability of sexual health services. Qualitative data were analysed using NVivo7. Results: Female sex workers target Latino migrant men in a wide variety of venues in urban and rural settings, directly soliciting clients where they live and work. Sex workers differ by ethnicity, venue, client occupation, and degree of mobility, with some sex workers appearing to be highly mobile throughout the region. Sex workers are predominantly Mexican, Dominican, and Central American women, but also include African-American and Caucasian women. Condom use appears to be relatively frequent among some sex workers and clients see Abstract P2-S2.04 Table 1 ; however, knowledge of HIV/STDs appears to be low among clients. There is a dearth of sexual health services available to sex workers and Latino migrant men. Conclusions: Latino migrant men and the female sex workers who serve them may be at increased risk for STD/HIV due to frequent mobility and lack of access to healthcare, including sexual health services. More research is needed to better understand how sex workers and clients interact in the South, and the risk and protective factors that affect HIV/STD outcomes. Recommendations included engaging local stakeholders to increase awareness of STD risk in these populations and address gaps in services.